KAJIAN PENGARUH CO-CREATION, CURRENCY, COMMUNAL ACTIVATION, DAN CONVERSATION TERHADAP KEPUASAN WISATAWAN DI PANTAI TLANGOH KABUPATEN BANGKALAN - Mohammad Izzulhaq; Nurul Arifiyanti; Resti Prastika Destiarni (JURNAL MATA PARIWISATA, 2025)
Tlangoh Beach is the third most visited tourist destination in Bangkalan Regency, offering great potential for development, but facing marketing challenges.. This study aims to analyze the impact of the 4C marketing mix concept (Co-Creation, Currency, Communal Activation, and Conversation) on tourist satisfaction at Tlangoh Beach, Bangkalan. The research uses a quantitative approach through a survey of 100 respondents obtained by the accidental sampling method. The data were analyzed using multiple linear regression. The results show that, simultaneously, the 4C marketing mix variables have a significant impact on tourist satisfaction. Co-Creation, Currency, and Communal Activation significantly influence, while Conversation does not. This is due to the lack of communication quality and responsiveness from the management.. This study recommends, among other things, exploring visitor preferences, providing suggestion boxes keeping up with social media trends, offering bundled tickets, community education packages, enabling online payments, activating social media, enhancing the destination's image, providing event spaces for communities, establishing complaint posts, and offering guides and lifeguards.